1996
DOI: 10.1007/bf00196818
|View full text |Cite
|
Sign up to set email alerts
|

Losses at 3p common deletion sites in subtypes of kidney tumours: histopathological correlations

Abstract: Deletions of the short arm of chromosome 3 (3p) have been recognized as characteristic features of clear cell renal cell carcinomas (clear cell RCC). We analysed 55 clear-cell RCCs and 30 non-clear-cell kidney tumours (10 papillary and 7 chromophobic RCCs, 11 oncocytomas and 2 collecting duct carcinomas) in loss of heterozygosity (LOH) studies using microsatellite markers for previously observed regions of common deletions on 3p in kidney tumours (3p25, 3p21.3, 3p14.2 and 3p12-13). Alterations were found in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…Accordingly, we selected markers close to the critical regions for homozygous 3p21 deletions in small cell lung cancer and two 3p14 markers contained within the FHIT gene. Our results are consistent with those of Lubinski et al (1994), Druck et al (1995), Hadaczek et al (1996), and van den Berg and Buys (1997), which have also demonstrated a high frequency of 3p14 and 3p21 LOH in CC-RCC and, coupled with reports (Killary et al, 1992;Sanchez et al, 1993) demonstrating suppression of tumourigenicity by the introduction of 3p fragments into cell lines, support a role for a 3p12-p21 TSG in RCC development. We found that the incidence of 3p25 LOH was lower in tumours without detectable VHL gene inactivation than in tumours with methylation or mutation of the VHL gene.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Accordingly, we selected markers close to the critical regions for homozygous 3p21 deletions in small cell lung cancer and two 3p14 markers contained within the FHIT gene. Our results are consistent with those of Lubinski et al (1994), Druck et al (1995), Hadaczek et al (1996), and van den Berg and Buys (1997), which have also demonstrated a high frequency of 3p14 and 3p21 LOH in CC-RCC and, coupled with reports (Killary et al, 1992;Sanchez et al, 1993) demonstrating suppression of tumourigenicity by the introduction of 3p fragments into cell lines, support a role for a 3p12-p21 TSG in RCC development. We found that the incidence of 3p25 LOH was lower in tumours without detectable VHL gene inactivation than in tumours with methylation or mutation of the VHL gene.…”
Section: Discussionsupporting
confidence: 95%
“…However, most studies have also reported that a proportion of tumours show discontinuous 3p allele loss with interstitial deletion at 3p25, 3p21, and 3p12-p14 (Foster et al, 1994b;Hadaczek et al, 1996;van den Berg and Buys, 1997). Localised areas of LOH are more likely to be found with an increased density of markers or if specific critical regions are targetted.…”
Section: Discussionmentioning
confidence: 90%
“…Mutations of the VHL gene are uncommon in these tumors as well. However, LOH analysis revealed 3p alterations in approximately 14% to 50% of papillary renal cell carcinomas [64,78,89]. DNA alterations that involve the long arm of chromosome 3 have been reported in both clear cell and papillary renal cell carcinomas.…”
Section: Papillary Renal Cell Carcinomamentioning
confidence: 96%
“…A minimal deletion of 1q32.1-32.2 was mapped in 57% to 69% of collecting duct carcinomas, suggesting that this region may contain a tumor suppressor gene involved in the carcinogenesis of collecting duct carcinoma [122]. LOH at the short arm of chromosome 3 is rarely detectable in collecting duct carcinoma [89,121]. Loss of chromosome arm 8p in clear cell renal cell carcinomas correlates with high stage and aggressive behavior; it may also be responsible for the poor prognosis of collecting duct carcinoma [121].…”
Section: Collecting Duct Carcinomamentioning
confidence: 99%
“…Loss of heterozygosity (LOH) analysis in six CDCs revealed allelic loss at chromosomes 8p and 13q in 50% of the tumors, and rarely at the short arm of chromosome 3 [12,13]. This data suggests that distinct genetic alterations from those observed in RCC, in which 3p LOH is common [14], occur in the development of this rare renal tumor.…”
Section: Introductionmentioning
confidence: 93%